People, Crops and Bee Farming: Landscape Models for a Symbiotic Network in Greece - Carydi, Io; Koutsianas, Athanasios; Desyllas, Marios (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Despite the rising awareness of the mutual benefits of pollination,agricultural production,and biodiversity,Greek planning has scarcely moved toward patterns of pollinator-friendly farm design models. This paper presents data from preliminary research analysis that defined generic landscape design models that can enhance the symbiotic associations between farming production and beekeeping in Greece. The main objective is to determine tailor-made landscape models that can contribute to a portfolio of actions easily apprehensible by non-technical audiences in the farming sector who want to introduce biodiversity enhancements to monoculture farming,fostering a safer,poisonous-free environment for introduced honeybees,simultaneously helping to augment their production yields. A preliminary study was conducted in four agricultural farming estates in Thessaly and the Peloponnese involving apple farming,citrus orchards,and hemp cultivation. It combined the analysis and assessment of land cover classes with regard to the provision of foraging habitat,assessment of foraging suitability,description of connectivity characteristics,and emerging spatial patterns of natural corridors,patches,and edges at an observation perimeter around each farm. Assessment of these data informed design models for planting enrichment and integration of natural patches,such as meadows and shrub corridors. Pilot installations of hives in study areas that combined characteristics of the landscape models presented resulted in the production of 8% to 12% bigger fruits and 30% to 50% increase in the total yield. We conclude that landscape design models for biodiversity enhancement are an important attribute of ecosystem services and require an understanding of specific geographical and landscape parameters to render models operational for bee farming and pollination.
Keywords: agricultural production; apiculture; biodiversity; crop production; farming system; landscape change; pollination; Greece; Biodiversity; Landscape connectivity; Landscape design models; Landscape ecology; Pollination; Regenerative agriculture; ODS 2 - Hambre cero; ODS 3 - Salud y bienestar; ODS 15 - Vida de ecosistemas terrestres